Molecular Mechanisms Driving IL-10- Producing B Cells Functions: STAT3 and c-MAF as Underestimated Central Key Regulators? - Michée-Cospolite, Magalie; Boudigou, Marina; Grasseau, Alexis; Simon, Quentin; Mignen, Olivier; Pers, Jacques-Olivier; Cornec, Divi; Le Pottier, Laëtitia; Hillion, Sophie (Frontiers in Immunology, 2022)
Regulatory B cells (Bregs) have been highlighted in very different pathology settings including autoimmune diseases, allergy, graft rejection, and cancer. Improving tools for the characterization of Bregs has become the main objective especially in humans. Transitional, mature B cells and plasma cells can differentiate into IL-10 producing Bregs in both mice and humans, suggesting that Bregs are not derived from unique precursors but may arise from different competent progenitors at unrestricted development stages. Moreover, in addition to IL-10 production, regulatory B cells used a broad range of suppressing mechanisms to modulate the immune response. Although Bregs have been consistently described in the literature, only a few reports described the molecular aspects that control the acquisition of the regulatory function. In this manuscript, we detailed the latest reports describing the control of IL-10, TGFβ, and GZMB production in different Breg subsets at the molecular level. We focused on the understanding of the role of the transcription factors STAT3 and c-MAF in controlling IL-10 production in murine and human B cells and how these factors may represent an important crossroad of several key drivers of the Breg response. Finally, we provided original data supporting the evidence that MAF is expressed in human IL-10- producing plasmablast and could be induced in vitro following different stimulation cocktails. At steady state, we reported that MAF is expressed in specific human B-cell tonsillar subsets including the IgD+ CD27+ unswitched population, germinal center cells and plasmablast.